Hábitos alimentares relacionados à sobrevida em nonagenários e centenários do AMPAL - Goulart, Luana de Souza (2020)
Introduction: Nonagenarians make up the fastest growing population group in Brazil. Deaths due to ill-defined signs and symptoms (25%) are the main causes of death of nonagenarians and centenarians, demonstrating a lack of assistance in these population groups. Aging is accompanied by changes in eating habits. Among nonagenarians and centenarians, the relationship of these habits to mortality is not established. Therefore, it is important to evaluate this relationship, providing a more adequate nutritional orientation that may be the result of a public health policy. Objective: To associate eating habits with survival in nonagenarians and centenarians. Methods: The 238 nonagenarians and centenarians, evaluated by the project “Multiprofessional Long-term Care in 2016, were followed up to August 2019 periodically by telephone or home visit. The number of months between the first assessment and the date of death or last contact was used to calculate follow-up time for survival analysis (by Cox damage regression). Eating habits were classified according to quality (Diet Quality Index - DQI) and diet variability (DVI). Results: The food intake evaluated by the DVI showed that chewing capacity (p=0.0033) and appetite (p=0.0368) influenced the index score. Age group (p=0.0247), physical exercise (p=0.0020), alcohol consumption (p=0.0344) and diarrhea (p=0.0064) were found to influence quality of the diet, reflecting on the DQI score. Both DVI and DQI were predictors of survival. Higher levels of both indices had a higher probability of survival, indicating significance for DVI (p=0.0809) and significant DQI (p=0.0098). Conclusions: Both quality and diet variability were predictors of survival in the nonagenarians and centenarians surveyed. It was possible to identify cutoff points for both indexes (DVI and DQI), more sensitive for survival prediction that could serve as normal parameters for the food quality of the nonagenarians and centenarians population. The DQI can be considered good of 9 or greater and the DVI if greater than or equal to 4. Although DQI had better performance both indices can be easily applied in primary care because they do not require specialized training. The instrument used for the calculation of indices is already widely applied in population surveys by IBGE. Therefore, the experience gained in the present work may be extended to other age groups.